2018
DOI: 10.1038/am.2017.212
|View full text |Cite
|
Sign up to set email alerts
|

N-doped carbon nanotubes containing a high concentration of single iron atoms for efficient oxygen reduction

Abstract: Fe-N-C has emerged as a promising noble-metal-free catalyst for the oxygen reduction reaction (ORR). However, achieving a catalytic activity comparable to that of Pt in acidic medium remains a great challenge. Here we report a N-doped carbon nanotube (CNT) catalyst in which a high concentration of single Fe atoms has been dispersed (CNT@Fe-N-PC). The catalyst was prepared by a simple and scalable atomic isolation method, in which a metal isolation agent was introduced to isolate Fe atoms and was then evaporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…The deconvolution method using Gaussian-Lorentz curve fittings was adopted to conduct the semiquantitative analysis of all the elements [ 37 , 38 ]. Figure 2(c) shows that the N and Fe contents were 5.02 at.% and 0.41 at.%, respectively, which correspond to previously published works of single-atom Fe-N-C materials [ 34 , 39 ]. The percentage of defective N configurations (pyridinic and pyrrolic N), regarded as coordination sites for single Fe atoms, was high.…”
Section: Resultssupporting
confidence: 86%
“…The deconvolution method using Gaussian-Lorentz curve fittings was adopted to conduct the semiquantitative analysis of all the elements [ 37 , 38 ]. Figure 2(c) shows that the N and Fe contents were 5.02 at.% and 0.41 at.%, respectively, which correspond to previously published works of single-atom Fe-N-C materials [ 34 , 39 ]. The percentage of defective N configurations (pyridinic and pyrrolic N), regarded as coordination sites for single Fe atoms, was high.…”
Section: Resultssupporting
confidence: 86%
“…[54] The common strategy for preparing the Fe SAs entails the utilization of Fe-containing organic precursors, followed by pyrolysis under high temperature. So far, reported Fe-containing organic precursors include Fe-bipyridine, [55] Fe-phthalocyanine, [56] Fe-zeolitic imidazolate framework (ZIF)-8, [57][58][59] Fe-polypyrrole, [60][61][62] Fe-porphyrinic triazine, [63] Fe-imidazole-melamine, [64] Fe-1,3,5-tris(4aminophenyl)-benzene/terephthaldehyde, [65] Fe-1,10 phenanthroline, [66] Fe-pyrrole-thiophene copolymer, [67] Fe-histidine, [68] Fe-porphyrinic MOFs, [69] Fe-phthalocyanine/unsubstituted phthalocyanine, [70] Fe-formamide, [71] Fe-tetra(4′-vinylphenyl) porphyrin, [72] Fe-bis(imino)-pyridine, [73] Fe-phthalocyanine/ ZIF-8, [74] Fe-melamine/lipoic acid, [75] Fe-polydopamine, [76] Feguanine, [77] Fe-polyoxyethylene-polyoxypropylene-polyoxyethylene (pluronic F-127), [78] Fe-glucosamine hydrochloride, [79] Fe-porphyra, [80] and ferrocene-ZIF-8. [81] For instance, Li et al reported a novel pyrrole/thiophene copolymer pyrolysis approach to synthesize the Fe-isolated SAs on sulfur and nitrogen co-doped carbon frameworks.…”
Section: Orrmentioning
confidence: 99%
“…To rationally design Fe-based SASCs, researchers are usually devoted to selecting special precursors that either already contain single-atom metal species or use the coordination between the complex ligands and surface groups of support materials [24,25]. Moreover, adsorbing iron ions to bulk materials or using a top-down synthetic method to peel off iron from metal bulk can also synthesize SASCs [26][27][28]. These methods have drawbacks of using expensive organic macromolecule complexes and running the risk of aggregating single-atom metal species into nanosized metal counterparts [29,30].…”
Section: Introductionmentioning
confidence: 99%